Incomensurabilidade sem paradigmas: a revolução epistemológica de Thomas Kuhn - Wolff Neto, Carlos Gustavo (Universidade do Vale do Rio do Sinos, 2007)
The general scenario of the philosophy of science in the 20th century was mainly determined by the epistemological traits of Logical Positivism and its verificationism, Popperian falsificationism, the Lakatian research programs, Paul Feyrebend’s epistemological anarchism, and Thomas Kuhn’s philosophy of science. Starting from this general scenario, this dissertation analyzes the main aspects of Thomas Kuhn’s philosophy of science, the spectrum of its critique by other thinkers, Kuhn’s response to that critique and the subsequent changes in Kuhn’s epistemology. Kuhn was involved in a fruitful debate on his ideas about scientific revolutions, normal science, paradigms, and incommensurability with some of the most important philosophers of the 20th century. This debate, which is discussed in the dissertation, prompted Kuhn to make changes in his original proposal as expounded in his most famous work, The Structure of Scientific Revolutions. These modifications and their scope are the main topic of the present
Incommesurability without paradigms:Thomas Kuhn’s epistemological revolution
Keywords: incomensurabilidade; léxico; taxonomia; Thomas Kuhn; revoluções científicas; lexicon; taxonomy; incommensurability; scientific revolutions; Ciências Humanas